The Influence of Insurance Literacy and Usefulness on Increasing Fire Insurance Products for Traders in the Market (Case Study of the Kampung Keling Market, Medan) - Siregar, Khidir; Imsar; Nasution, Juliana (Universitas Ibn Khladun Bogor, 2024)
Many variables, such as inadequate socialization and education, might contribute to the issue of low fire insurance literacy. Therefore, the local populace still knows very little or nothing about fire insurance. With a case study of the Kampung Keling market in Medan, this study attempts to ascertain the impact of insurance literacy and usefulness on boosting fire insurance products for traders in the market. In this study, a descriptive methodology is combined with a quantitative approach. 96 merchants at Pasar Kampung Keling Medan were surveyed in order to get the study data. Multiple linear regression was used to evaluate the data. The findings indicated that the applicability and favorable impact of insurance literacy on the uptake of fire insurance products by Pasar Kampung Keling Medan traders was noteworthy. This demonstrates how traders' interest in insurance goods may rise when they are informed about the advantages of insurance and have pleasant insurance-related experiences.